2007
DOI: 10.1111/j.1440-1681.2007.04831.x
|View full text |Cite
|
Sign up to set email alerts
|

Δ‐opioid Receptor Stimulation Enhances the Growth of Neonatal Rat Ventricular Myocytes via the Extracellular Signal‐regulated Kinase Pathway

Abstract: 1. The aims of the present study were to determine whether delta-opioid receptor stimulation enhanced proliferation of and to investigate the role of the extracellular signal-regulated kinase (ERK) pathway in ventricular myocytes from neonatal rats. 2. At concentratins ranging from 10 nmol/L to 10 micromol/L, [D-Ala2,D-Leu5]enkephalin (DADLE) concentration-dependently promoted myocardial growth and DNA synthesis and altered the cytoskeleton. 3. At 1 micromol/L, DADLE also increased the expression and phosphory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 48 publications
1
11
0
1
Order By: Relevance
“…In the opioid receptor superfamily, the δ receptor is closely associated with the viability and proliferation of cells (32,33). As demonstrated in previous studies, the activation of the δ receptor promotes the proliferation of rat ventricular muscle cells (34,35). In the current study, alpinetin was administered to rat myocardial cells, leading to an increase in the expression level of the δ receptor, a significant reduction in the myocardial apoptosis rate and an increase in cell proliferation.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In the opioid receptor superfamily, the δ receptor is closely associated with the viability and proliferation of cells (32,33). As demonstrated in previous studies, the activation of the δ receptor promotes the proliferation of rat ventricular muscle cells (34,35). In the current study, alpinetin was administered to rat myocardial cells, leading to an increase in the expression level of the δ receptor, a significant reduction in the myocardial apoptosis rate and an increase in cell proliferation.…”
Section: Discussionsupporting
confidence: 73%
“…It was demonstrated in a previous study that the δ receptor acted via the ERK signaling pathway to promote the survival and proliferation of cells (35). In this study, we proposed that alpinetin exerted its protective effects on the rat myocardial cells by exciting the δ receptor to activate PKC, leading to the further activation of ERK.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Zhao et al (37) found that opioid receptors promote cell survival and proliferation via the ERK1/2 pathway. We determined that the activation of the δ-opioid receptor enhances PKC expression.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of cardiac G-protein coupled delta opioid receptors (DOR) induces an intracellular kinase pathway in which activation of mitochondrial ATP-sensitive K + -channels seem to play an important role [8][9][10]. In addition, DOR activation triggers different mechanisms at multiple levels to stabilize homeostasis, to increase pro-survival signaling and antioxidative capacity, and to stimulate the growth of neonatal rat ventricular myocytes [11][12][13].…”
Section: Introductionmentioning
confidence: 99%